Formação do técnico de enfermagem para administração segura de medicamentos: proposição de tecnologia educacional virtual - Simão, Milena Agostinho Tunes [UNESP] (2015)
This study focuses, as a theme, the safe medications administration, choosing the teaching-learning process of this subject in technical nursing courses, as its object. The objective was to identify, in the current scientific literature and in the interviews with teachers of these courses, how the technical education in nursing must be, in order to develop competence in safe medication administration, with a view to propose subsidies for virtual educational technology development, to be inserted as a curricular activity. The study methodology involved two stages: initially, an integrative review of national and international literature, published in the last five years on the subject of this study was held and its insertion in nursing education, then, interviews with 10 nursing teachers of three technical nursing courses, were conducted, these ones from different towns in São Paulo state, who were linked to a private educational institution, where the author works as a teacher. The material, obtained by integrative review, was descriptively characterized as the publishing and structure aspects, and its findings, conclusions and recommendations were organized into categories built according to convergences on the question: How must nursing education for safe practice in the medications administration be? The testimonials of teachers were organized according to the Content Analysis method, thematic strand. The synthesis of all material was discussed based on current assumptions of Patient Safety Promoting and on the existing policy guidelines of Nursing Education Technical Level. The 21 reviewed articles and the testimony of 10 surveyed teachers revealed varied evidences on safe care in medication process (Theme 1), as well as the development of this professional competence in technical nursing courses (Theme 2). The collected data confirms the importance of the issue in relation to nursing ...